2022
DOI: 10.2807/1560-7917.es.2022.27.46.2200845
|View full text |Cite
|
Sign up to set email alerts
|

Large increase in bloodstream infections with carbapenem-resistant Acinetobacter species during the first 2 years of the COVID-19 pandemic, EU/EEA, 2020 and 2021

Abstract: Recent data from the European Antimicrobial Resistance Surveillance Network (EARS-Net) show a large increase of +57% in Acinetobacter species bloodstream infections in the European Union and European Economic Area in the first years of the COVID-19 pandemic (2020–2021) compared with 2018–2019. Most were resistant to carbapenems, from intensive care units, and in countries with ≥ 50% carbapenem resistance in Acinetobacter spp. in 2018–2019. This highlights the requirement for reinforced Acinetobacter preparedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Recent data from the European Antimicrobial Resistance Surveillance Network (EARS-Net) show a large and statistically significant increase of Acinetobacter spp. BSIs in the European Union (EU) and European Economic Area (EEA) during 2020–2021 (+ 57% compared to 2018-2019), a period which represents the first years of the COVID-19 pandemic [ 4 ]. In a systemic review of pan-drug-resistant (PDR) Gram-negative bacteria epidemiology and prognosis, Pseudomonas aeruginosa and A. baumannii were the most common PDR reported species (33%), followed by Klebsiella pneumoniae (24%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from the European Antimicrobial Resistance Surveillance Network (EARS-Net) show a large and statistically significant increase of Acinetobacter spp. BSIs in the European Union (EU) and European Economic Area (EEA) during 2020–2021 (+ 57% compared to 2018-2019), a period which represents the first years of the COVID-19 pandemic [ 4 ]. In a systemic review of pan-drug-resistant (PDR) Gram-negative bacteria epidemiology and prognosis, Pseudomonas aeruginosa and A. baumannii were the most common PDR reported species (33%), followed by Klebsiella pneumoniae (24%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…in 2018–2019, experienced the most noticeable increases (+116%) in Acinetobacter spp. BSIs in 2020–2021 compared with 2018–2019 and suggested surveillance at local, national and EU/EEA levels to monitor whether this worrying development is halted or even reversed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic led to significant changes in AMR trends for invasive isolates [ 7 , 8 ]. A recent study by the ECDC revealed a large increase in CRAb in the European Union and European Economic Area during the first two years of the pandemic [ 14 ]. The latest ECDC EARS-Net data (up to 2022) show that CRAb has increased in blood cultures in Slovenia and all neighboring countries, with the exception of Austria.…”
Section: Discussionmentioning
confidence: 99%
“…BSI in the EU and European Economic Area (EEA) in the first years of the COVID-19 pandemic (2020–21) compared with 2018–19. 4 Additionally, among isolates from ICUs in countries with high (≥50%) prevalence of carbapenem-resistant Acinetobacter spp., carbapenem resistance increased from 73.2% to 85.6% over this 3 year period. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Additionally, among isolates from ICUs in countries with high (≥50%) prevalence of carbapenem-resistant Acinetobacter spp., carbapenem resistance increased from 73.2% to 85.6% over this 3 year period. 4 …”
Section: Introductionmentioning
confidence: 99%